(untitled) (Journal of the College of Basic Education, 2022)
A historian is usually concerned with real events that truly happened in the past and, therefore, his writings should present a realistic picture of past eventsas they had truly happened. A historical romancer, on the other hand, is basically committed to being less realistic and more imaginative in presenting his point of view of life and of past events.